Surgical management challenges and clinical results of bimanual micro-incision phacoemulsification cataract surgery in children with congenital cataract - Amon, M (Nepalese Journal of Ophthalmology, 2011)
Introduction: Small incisions in cataract surgery have shown to reduce tissue damage, postoperative inflammation and pain. Objective: To describe in detail the surgical management challenges and clinical results of bimanual micro-incision phacoemulsification cataract surgery in children with congenital cataract. Materials and methods: In 22 eyes of 14 children aged from 11 months to 17 years with congenital cataract, micro-incision cataract surgery with lensectomy, bimanual aspiration or phacoemulsification and implantation of an intraocular lens (SN60WF, Alcon®) was performed under general anesthesia. The visual equivalent obtained with age-related methods, the slit-lamp examination, and refractive outcome were documented in the medical records and were analyzed retrospectively. The patients fulfilled at least 3 months of follow up. Results: In all operated eyes, micro-incision cataract surgery could be performed without serious intra-operative complications. Lensectomy was safely combined with a primary posterior capsulorhexis and anterior vitrectomy in 17 of 22 eyes. Corneal incision length ranged between 2.2 mm and 2.6 mm (mean: 2.3 ± 0.2 mm). No cases of postoperative hypotony and increased inflammation were observed. One eye required surgical removal of the after-cataract 7 months after surgery. Laser capsulotomy for posterior capsular opacification had to be performed in 2 (9 %) eyes. In all other eyes (19/22), visual axis remained clear during follow-up.Conclusion: Micro-incision cataract surgery is a promising alternative to conventional pediatric cataract surgery, since the technique showed to be comparably safe and effective. Longer follow-up examinations will now be performed.Key words: congenital cataract; bimanual micro-incision phacoemulsificationDOI: 10.3126/nepjoph.v3i1.4270Nepal J Ophthalmol 2011;3(5):3-8